Áp dụng tính chất của dãy tỉ số bằng nhau , ta có :
\frac{a}{2012}=\frac{b}{2013}=\frac{c}{2014}=\frac{a-b}{2012-2013}=\frac{b-c}{2013-2014}=\frac{c-a}{2014-2012}2012a=2013b=2014c=2012−2013a−b=2013−2014b−c=2014−2012c−a
\Rightarrow\frac{a-b}{-1}=\frac{b-c}{-1}=\frac{c-a}{2}⇒−1a−b=−1b−c=2c−a
\Rightarrow\left(\frac{a-b}{-1}\right)\left(\frac{b-c}{-1}\right)=\left(\frac{c-a}{2}\right)^2⇒(−1a−b)(−1b−c)=(2c−a)2
hay \left(a-b\right)\left(b-c\right)=\frac{\left(c-a\right)^2}{4}(a−b)(b−c)=4(c−a)2
\Rightarrow4\left(a-b\right)\left(b-c\right)=\left(c-a\right)^2⇒4(a−b)(b−c)=(c−a)2
Áp dụng tính chất của dãy tỉ số bằng nhau , ta có :
\frac{a}{2012}=\frac{b}{2013}=\frac{c}{2014}=\frac{a-b}{2012-2013}=\frac{b-c}{2013-2014}=\frac{c-a}{2014-2012}
\Rightarrow\frac{a-b}{-1}=\frac{b-c}{-1}=\frac{c-a}{2}
\Rightarrow\left(\frac{a-b}{-1}\right)\left(\frac{b-c}{-1}\right)=\left(\frac{c-a}{2}\right)^2
hay \left(a-b\right)\left(b-c\right)=\frac{\left(c-a\right)^2}{4}
\Rightarrow4\left(a-b\right)\left(b-c\right)=\left(c-a\right)^2
Đặt \(\frac{a}{2012}=\frac{b}{2013}=\frac{c}{2014}=k\)
\(\Rightarrow a=2012k,b=2013k,c=2014k\)
\(\Rightarrow4\left(a-b\right)\left(b-c\right)=4\left(2012k-2013k\right)\left(2013k-2014k\right)\)
\(=4\left(-k\right)\left(-k\right)\)
\(=4k^2\left(1\right)\)
Mặt khác:\(\left(a-c\right)^2=\left(2012-2014\right)^2\)
\(=\left(2k\right)^2\)
\(=4k^2\left(2\right)\)
Từ (1),(2) suy ra.......